City marketing in various fields of schoolar: The development of periodical concept and definition - Aisah Asnawi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
City marketing is a topic that attracts many researchers from various scholars. Some of them include management, urban planning, geography, communication science, and urban development. this is very interesting because the sliced theory of city marketing is very specific to each field of science. It is undeniable, the definition of city marketing is also growing from year to year. This research has an aim to mapping the concept and definition of city marketing from year to year to see the focus of discussion and the objectives of the city marketing strategy. The definition changes occur every year but the main focus of city marketing remains on the citizen, visitors, and investors. This is related to the function of a city as a place that is worth living, worth visiting and worth investing. Besides, the understanding that a city can be marketed like a product is highly inappropriate over time because the city has stakeholders and functions that are more complex than marketing in general. Based on the analysis of the chronology, the development of the city marketing concept has continues into several new concepts including city branding. The definition and concept also evolved since 1960 by Kevin Lynch but this paper divided into three periods, those are years 1982-1999, years 2000-2010, and years 2011-2018. During the period 1960 to 1980, the concept of city marketing was still influenced by Kevin Lynch so that not too many new concepts were developed